Photo Albums of the 1880 Zagreb Earthquake - Damjanović, Dragan (Array, 2014)
The earthquake that hit Zagreb on 9th November 1880 was one of the most important breakpoints in the history of architecture and urban planning of the city. It was estimated that in its epicenter, which was northeast of Zagreb, earthquake was of magnitude 6.2 on the Richter scale. Barely any building in the city remained undamaged, and many buildings had to be completely removed due to the danger of collapse. On third day after the tragic event, Zagreb photographers began photographing significantly damaged or destroyed buildings. Otto Dasch made the first photographs and was soon after followed by other esteemed Zagreb photographers: Hinko Krapek, Gjuro Varga, Hermann Fickert and Johann (Ivan) Standl. Photographers played a key role in disseminating visual information about the earthquake, which was the only event that enticed a rather great interest of the world press for the Croatian capital in the second half of the 19th century. Although the earthquake did not have catastrophic effects, early reports of the majority of German, Hungarian, French, Italian, English and Slovenian dailies were rather unreliable, and often replete with exaggeration. The news appearing after the primary fear toned down, was completely contrary to the previous reports in that they minimized the damage. The aforementioned photographers thus tried with their photos to contribute to the objective view of the situation. However, they shot almost only those buildings which were most severely damaged by the earthquake, not so much because they wanted to overemphasize the scale of the destruction but because such scenes were the most interesting for the audiences. That was the same reason illustrated magazines from different parts of the world published images showing the most damaged buildings. During 1881, three albums were made which showed photographs of the earthquake damaged buildings. Two of them contain works of Standl and Fickert respectively, while the third album is a collection of works by four photographers: Standl, Fickert, Varga and Dasch. Standl's album “Photographs of the Zagreb Earthquake“ is characterised by a great quality of photos. It contains 25 works which were mostly commissioned by the Yugoslav (today Croatian) Academy of Sciences and Arts where Standl worked as an official photographer. Academy's Institute for Mathematics and Physics started gathering information about the earthquake in mid-November, at the same time when Standl was commissioned to take photographs of damaged buildings. The aim was to keep memory on the earthquake and to facilitate its scientific research. Standl’s album has been preserved in a rather large number of copies in various public institutions (archives, museums) and in private collections. Contrary to Standl, Fickert created his album “Memories on the Zagreb earthquake on 9th November 1880“ through his personal efforts and initiative. Each buyer of the album could choose 15 photographs from Fickert's collection and thereby create his or her own album, which consequently led to the creation of several different compilations of Fickert's works. The album containing the works of all three photographs bears the title “Photos of the Zagreb Earthquake on 9th November 1888“. It was created most likely due to the efforts of a public institution, probably the Zagreb City Council. Its special value lies in the photographs taken by Gjuro Varga which show damaged buildings on Zagreb's main city square. The aim of this presentation is an analysis of the creation and content of the photos from the albums and an attempt to present the ways in which the photos influenced the formation of the event’s image.